Exploring factors influencing post-partum length of hospital stay among women residing in two high priority districts of Uttar Pradesh: a quantitative study - Pandey, Anuj Kumar; Pachouri, Shalu; Pandey, Anvita (International Journal of Research in Medical Sciences, 2020)
Background: The first hour and day following childbirth is a period of rapid change within child and mother, with a potential for immediate crises as more than half of global maternal deaths occur during the postnatal period, of which 45 percent maternal and three- quarters of neonatal deaths occur within one day after deliver. Despite of the importance of this period, less than half of mother and newborn get the checkup done in first 24 hours in the state of Uttar Pradesh in India. This quantitative study explored the factors associated with early postpartum hospital discharge. Methods: This was a hospital-based study in which exit interviews were done using structured questionnaire from 278 recently delivered women at two randomly selected Community Health Centres of Gonda and Bareilly districts each, from Uttar Pradesh. The outcome variable was duration of hospital stay. Descriptive results were presented with comparison of factors within district, followed by bivariate analyses and linear regression was done to adjust for confounders. Results: Longer distance of house from facility (0.07; 95 percent CI 0.04, 0.01; p<0.001), if informed about new-born care (0.49; 95 percent CI 0.01, 0.85; p 0.01), if ASHA had fewer visits to women house (-0.06; 95 percent CI -0.12, -0.1; p 0.01) were found to be the determinant of longer stay after adjusting for all variables that were found significant in bivariate analysis and were biologically plausible. Conclusions: The present study concludes that there is lack of awareness among women and their relatives. Inadequate information provided by front line workers were some of the major factors influencing hospital stay pattern.